Geospatial Analysis of Lightning Incident Zoning in Bangladesh - Hafsa, Bibi; Kakon, Faria Akter; Prokrity, Hafsa Mehjabin; Islam, Md. Sazzadul; Rafi, Md. Rafsanur (The Jahangirnagar Review, 2025)
Lightning is one of the deadliest natural hazards in Bangladesh, claiming hundreds of lives annually and causing significant damage to infrastructure, especially in rural areas. This study presents a comprehensive analysis of lightning incidents across Bangladesh from 2017 to 2020, utilizing Geographic Information Systems (GIS) for spatial and temporal analysis. The primary objective of the study is to identify high-risk zones and temporal patterns to aid in the prediction and mitigation of lightning-related hazards. The study incorporates data from meteorological agencies, newspaper reports, and government databases, analyzing the frequency, intensity, and distribution of lightning incidents. Using advanced GIS tools such as Moran’s I for spatial autocorrelation and kriging interpolation for spatial distribution, the study identifies regions where lightning strikes are most prevalent and investigates the seasonal patterns of these incidents. The findings reveal that lightning incidents are highly clustered in specific regions, particularly during the pre-monsoon and monsoon seasons, with divisions like Sylhet, Khulna, and Rajshahi being disproportionately affected. Moreover, the results indicate a rise in lightning incidents over the study period, likely influenced by changing climatic conditions. The analysis provides valuable insights for policymakers and disaster management authorities, highlighting the need for region-specific interventions and public awareness campaigns. By mapping lightning-prone areas and identifying temporal trends, the report contributes to the development of targeted strategies to reduce lightning-related deaths and injuries, enhancing overall public safety in Bangladesh.